The Relationship between Knowledge and Attitudes with Stigma to People with Schizophrenia (PWS) - Esty Febriani; Abigael Ati; Danny Setyawan; Citra Fitri; Hartono Rakiman; Shaqina Said; Mivtahurrrahimah Mivtahurrrahimah (Universitas Ahmad Dahlan, 2024)
Stigma contributes to low treatment compliance in people with schizophrenia (PWS). Community surveys (N=180 PWS neighbors) of the Lentera Health Nusantara Foundation were used to analyze the relationship between knowledge of and attitudes toward the PWS stigma from March to December 2020 in the Sidoarjo and Ponorogo Regencies in East Java Indonesia. This cross-sectional study using questionnaires focused on knowledge related to symptoms, causes, and treatment as well as attitudes that describe the stigma toward PWS. The study revealed that only half of the respondents from Ponorogo (57.8% and 58.9%) and Sidoarjo (58.9% and 58.9%) had relatively good knowledge and attitudes, which shows that there is still a stigma toward PWS in the community. Furthermore, respondents in Sidoarjo were 0.019 times (98.1% lower) more likely to have a negative attitude (stigma) toward PWS than respondents in Ponorogo. There is a need for a sustainable and comprehensive strategy involving stakeholders, including health facilities, governments, and communities, especially those in rural areas, to overcome this problem of increasing compliance with PWS treatment and ensuring that the condition of the PWS is stable.